Petrological and Geochemical Characteristics of the Lower Cambrian Shuijingtuo Formation in the Middle Yangtze Block, South China: Implications for Organic Matter Accumulation on Carbonate Platform - Baomin Zhang; Quansheng Cai; Guotao Zhang; Oumar Ibrahima Kane; Lin Chen; An Liu; Peng Zhou; Ruyue Wang (Journal of Marine Science and Engineering, 2026)
Understanding the development characteristics and controlling factors of organic-rich shales in carbonate platform settings is essential for predicting their distribution and assessing their natural gas exploration potential. However, the mechanisms governing the accumulation of such shales in these specific sedimentary environments remain poorly constrained, and the lack of integrated petrological and geochemical studies limits accurate evaluation of their resource potential. The key objective of this study is to investigate the development characteristics and formation mechanisms of organic-rich shales within intraplatform depressions. To address this objective, we conducted a comprehensive petrological and geochemical analysis of the Cambrian Shuijingtuo Formation organic-rich shale deposits deposited in a carbonate platform setting, particularly from Well EYY3 in Western Hubei, Central Yangtze region. The obtained results indicate that total organic carbon (TOC) contents in the Shuijingtuo Formation can reach up to 4.77%, with a thickness of approximately 9.5 m for shales containing over 2% TOC. Vertically, TOC content exhibits a rapid increase at the base, followed by a gradual decline toward the top, reflecting the evolution of depositional environments. The characteristics of organic-rich shale indicate a significant presence of carbonate minerals, which increase in concentration, alongside tuff lenticular bodies and lithological transition surfaces between tuff and shale. While the longitudinal variation of SiO2 content in shale is subtle, there is a slight increase in land-sourced clasts and excess silica, and TOC has a significant positive correlation. At the base of the Shuijingtuo Formation, redox parameters, including U-EF and Mo-EF, display a rapid increase followed by a gradual decrease. Conversely, changes in Ni-EF, which indicate paleoproductivity, are less pronounced, and their correlation with TOC is relatively poor. These findings suggest that rapid sea-level rise associated with Cambrian transgressions was the main factor influencing organic matter enrichment in the carbonate platform depressions. This rise supplied nutrients and silica-rich organisms, altering the biological landscape and fostering anoxic conditions in the intraplatform depressions, promoting organic-rich shale formation. As sea levels declined, water circulation became restricted, leading to oxidation of shallow water bodies, decreased paleoproductivity, and shale deposits transitioned to tuff. Therefore, organic-rich shale can also be developed on carbonate platforms, with its formation primarily controlled by fluctuations in sea level. During highstand periods, intraplatform depressions may serve as favorable zones for shale gas exploration.